Understanding the depleting and replenishing effects of compassion on resources and stress recovery - SIM, Samantha Su-Hsien (Institutional Knowledge at Singapore Management University, 2017)
Existing literature on compassion in the workplace examines the antecedents of compassion and compassionate organizing with the underlying assumption that compassion for the suffering of others is a positive emotion and has desirable outcomes. I challenge this assumption by conceptualizing compassion as an ambivalent emotion and exploring the effects of compassion on individuals who feel compassion. Using an experience-sampling methodology, outcomes such as helping behaviour, regulatory resources, personal resources, and stress response are examined. Feeling compassion for others can be distressing and requires emotional regulation. At the same time, feeling compassion can also motivate behaviours to alleviate suffering. Thus feeling compassion may initially be depleting yet be paradoxically later experienced as replenishing through the increased personal resources associated with helping others. However, whether there are constraints to helping also matters as feelings of compassion are not always acted on. Feelings of compassion should not translate into helping behaviour and should not lead to increased personal resources if constraints to helping are high. Further, conceptualizing compassion as an ambivalent emotion encompassing both pleasant and unpleasant aspects suggests that the emotion has some positive effects such as resilience and improved stress recovery. Using an experience sampling method, or daily diary method, the effects of compassion on the aforementioned outcomes were examined on a sample of 80 university undergraduates over nine days. The results of the study suggest that compassion feelings and compassion behaviours have different effects on outcomes. The results of the study also suggest that feeling compassion for others has no significant effects on depletion whereas behaving compassionately is replenishes as it significantly increases personal resources. The results of the study also suggest that constraints to compassion behaviour can reduce the replenishing effects on personal resources. The results of the study also find that compassion increases mixed emotion which in is related to improved stress recovery. The study contributes in providing results that distinguish between compassion feelings and compassion behaviour, as well as being the first to examine within-person fluctuations of compassion feelings and behaviour. The study has implications on organizational citizenship behaviours as well as for organizations interested in building compassion cultures.